Beecoming Modern - Maue, Ellie; Marshall, Jeremy (My University, 2018)
As an architecture student I am constantly looking at nature for design inspirations, and my search often leads me to the structure and design of bees. These tiny creatures are some of the best builder, but their habitat is being destroyed day after day by human development. To combat this, “bee blocks” are often used to provide shelter for the bees, so that they can hibernate and remain undisturbed. However, these blocks lack the ingenuity and complex design ability that bees used to place in their structures. So, in order to regain what they lost, I decided to reimagine the traditional bee block. ! Accomplish this goal involved researching the previous man-made and bee-made structures was crucial, along with finding out key elements required to build this structure so that it is safe for bees. After doing this research, I then worked on redesigning it in a way that drew inspiration from original bee structures, without losing its actual functionality. This ended with a sculpture like design, that is fully functional, and relatively easy to build; making it a structure both worthy of the bee’s presence, easy for the average individual to build, and perfect in helping preserve future bee populations.
Keywords: Fall 2018